Feeding Tall Fescue Seed Reduces Ewe Milk Production, Lamb Birth Weight and Pre-Weaning Growth Rate - Jessica L. Britt; Maslyn A. Greene; Sarah A. Wilbanks; J. Keith Bertrand; James L. Klotz; William Bridges; Glen Aiken; John G. Andrae; Susan K. Duckett (Animals, 2020)
Endophyte-infected tall fescue (E+) produces ergovaline and ergovalinine, which are mycotoxins that act as dopamine agonists to suppress prolactin and induce vasoconstriction. The experiment was designed as a 3 × 2 × 2 factorial with DRD2 genotype (AA, AG, GG), fescue seed (endophyte-free, E− or endophyte-infected, E+), stage of gestation (MID, d (day) 35–85; LATE, d 86–parturition) and all interactions in the model. Pregnant Suffolk ewes (n = 60) were stratified by genotype and fed E+ or E− seed in a total mixed ration according to treatment assignment. Serum prolactin concentrations were lower (p < 0.05) in ewes fed E+ seed but did not differ by maternal DRD2 genotype or two-way interaction. Lamb birth weight was lower (p < 0.05) in ewes fed E+ seed in last trimester. Pre-weaning growth rate, milk production and total weaning weight was reduced (p < 0.05) in ewes fed E+ fescue seed during MID and LATE gestation. Ingestion of ergovaline/ergovalinine in last trimester reduces lamb birth weight; however, lamb growth rate, milk production and total weaning weight are reduced in all ewes fed E+ during mid and last trimester.